MENGANALISIS MATERI PADA BUKU SUPER DEUTSCH DENGAN TEMA KULINARISCHE REISEN BERDASARKAN CAPAIAN PEMBELAJARAN PERMENDIKBUD FASE F - Fiolina Manurung; Dorie Evelyn Zebua; Meilani Veronika Sinaga; Mei Sinta Kartini Sitorus (Argopuro: Jurnal Multidisiplin Ilmu Bahasa, 2025)
This study examines the alignment of Chapter III "Kulinarische Reisen" in the Super Deutsch textbook for grade XII with the chapter's learning objectives and the Learning Achievement Standards (CP) for German Language Phase F outlined in the Ministry of Education and Culture (Permendikbud) regulations. Content analysis reveals that while the chapter introduces vocabulary and grammar related to culinary travel, its level remains at A1, falling short of the stated learning objectives and CP for Phase F. The study identifies a lack of complex speaking and writing] exercises and a focus on basic vocabulary and grammar structures, which are insufficiently challenging for grade XII students. However, the material has potential for improvement. The study recommends adding more complex speaking and writing exercises, integrating deeper German cultural elements, and increasing the difficulty level of the material to better align with the learning objectives and CP for Phase F.